(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study aimed to extract apple juice from green apple fruits that had been treated by blanching. The usual thermal process, before storing the extracted juice at a temperature of (4)?, for a period of (30) days, and comparing it with the juice of untreated fruits in order to determine the effect of inhibiting the enzyme polyphenol oxidase in apple fruits with the treatments which mentioned in some properties of PPO (Polyphenol oxidase). Apple juice which extracted from these fruits, and the characteristics studied are: Residual Enzymatic Activity, Total Soluble Sugars, Ascorbic Acid content, Total Phenols Content, and Browning Index, as blanching the fruits in the usual way had a significant effect in reducing the remaining Activity Enzymatic and Ascorbic Acid values ??of the juice of the treated fruits, While the Total Soluble Sugars and Total Phenols content had a significant increase in their values ??after the end of the storage period, as for the Browning Index values . It was not affected at the end of the storage.process